The tangible and intangible values of river towards sustainable urban landscape development - Mohd. Hussain, Mohd. Ramzi (Kulliyyah of Architecture and Environmental Design, IIUM, 2012)
This paper presents a review on the tangible and intangible values of river towards sustaina-ble urban landscape development. The frame-work incorporated ecological knowledge related to river and sustainable planning and design process, rivers as an urban greenways corridor and green patches, river as urban heritage con-servation, rivers and riverfront development and theory from the Islamic perspectives. The objec-tive of the paper is to identify the functional and spatial structure of the existing river with respect to the requirements for harmonious develop-ment, protection and improvement of the sus-tainable urban landscape. It is also to provide important ecological and aesthetic benefits of river in urban setting. This study presents an understanding for facilitating protection, preser-vation, restoration, ecological enhancement of the river into a more comprehensive land-use planning process.